Transformation and Depuration of Paralytic Shellfish Toxins in the Geoduck Clam Panopea globosa From the Northern Gulf of California - Medina-Elizalde, Jennifer; García-Mendoza, Ernesto; Turner, Andrew D.; Sánchez-Bravo, Yaireb Alejandra; Murillo-Martínez, Ramón (Frontiers in Marine Science, 2018)
In January 2015, a harmful algae bloom (HAB) of the dinoflagellate Gymnodinium catenatum occurred in the Northern Gulf of California (NGC). This species produces paralytic shellfish toxins (PSTs), a group of potent neurotoxins. The harvesting and commercialization of geoduck Panopea globosa are important economic activities in this region and were prohibited for several months due to the accumulation of PSTs in clam tissues. We analyzed PSTs concentrations in P. globosa collected on a weekly basis during 2015 near San Felipe, Baja California. The aim of the study was to evaluate the transformation and depuration characteristics of PSTs in different geoduck tissues. The PST content was evaluated in the visceral mass and in the siphon by high-performance liquid chromatography with post-column oxidation (HPLC-PCOX). Additionally, 10 selected samples were analyzed by hydrophilic interaction chromatography coupled to tandem mass spectrometry (HILIC-MS/MS). Toxicity in all siphon samples was lower than the regulatory limit (RL) for PSTs of 800 μg STX eq kg-1. In contrast, the maximum toxicity of 16,740 μg STX eq kg-1 detected in the visceral mass exceeded 21 times the RL and it took 210 days to reach values below 800 μg STX eq kg-1. Therefore, P. globosa can be considered a slow detoxifier bivalve with a depuration rate of 4.3% day-1 (calculated by an exponential decay model; R2 = 0.80). The N-sulfocarbamoyl toxins C1 and 2 were the most abundant analogs in the siphon and viscera samples collected close to the HAB occurrence. The concentration of these analogs decreased and GTX5 and more toxic analogs such as dcGTX2 and dcSTX were detected. M-type analogs were detected by HILIC-MS/MS and represented up to 75% of total PSTs in some samples. M-type analogs contributed to 48% of toxicity estimated in the sample. We report for the first time the depuration rate, PSTs profile, and its change over time in P. globlosa. This information is essential to characterize the metabolism of toxins in this economically important bivalve but also to develop management plans for fisheries if the organism is going to be recurrently exposed to PSTs producing blooms, as seems the case for the NGC.